Argonauts of the western Pacific - Malinowski, Bronislaw, 1884-1942., author.
1 online resource (xviii, 541 pages)
Keywords: "Bronislaw Malinowski's pathbreaking Argonauts of the Western Pacific is at once a detailed account of exchange in the Melanesian islands and a manifesto of a modernist anthropology. Malinowski argued that the goal of which the ethnographer should never lose sight is 'to grasp the native's point of view, his relation to life, to realise his vision of his world.' Through vivid evocations of Kula life, including the building and launching of canoes, fishing expeditions and the role of myth and magic amongst the Kula people, Malinowski brilliantly describes an inter-island system of exchange - from gifts from father to son to swapping fish for yams - around which an entire community revolves. A classic of anthropology that did much to establish the primacy of painstaking fieldwork over the earlier anecdotal reports of travel writers, journalists and missionaries, it is a compelling insight into a world now largely lost from view. With a new foreword by Adam Kuper"--